Preparation of titanium-based composite material continuous core net structure wire material for fuse wire additive manufacturing
By using the continuous core mesh structure wire preparation method of titanium tape and embedded mesh reinforcement powder in titanium-based composite additive manufacturing, the problems of expensive powder raw materials and low material density in titanium-based composite additive manufacturing are solved, and the preparation of titanium-based composite wire with high strength and high material utilization is achieved.
Patent Information
- Application Number
- CN202411739190.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing additive manufacturing technology of titanium-based composite materials has problems such as expensive powder raw materials, low material density and difficulty in achieving the anisotropy of continuous fiber-reinforced titanium-based composite materials.
A titanium-based composite material powder with a pure titanium alloy tape as the outer titanium shell and a titanium-based composite material embedded in a fine mesh reinforcement is used as the fill powder. The continuous core mesh structure wire is prepared by sealing rolling and drawing reduction, and in-situ self-generating reinforcement is performed using fuse additive manufacturing method.
The high-strength and tough titanium-based composite wire preparation has been achieved, which solves the problems of difficult deformation and low plasticity of titanium alloys, improves the utilization rate of materials and additive manufacturing efficiency, and is suitable for integrated forming of large structural parts.
Smart Images

Figure CN119525516A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal-based composite materials, and in particular to a method for preparing a titanium-based composite material continuous core mesh structure wire for fused wire additive manufacturing. Background Art
[0002] The next generation of high-end aerospace equipment faces extremely harsh conditions such as ultra-high temperature, large overload, and strong vibration, and there is an urgent need to develop lightweight, high-strength, and heat-resistant new materials and related integrated manufacturing technologies. Titanium-based composites (TMCs) are discontinuously reinforced titanium-based composites (TMCs) formed by introducing multi-dimensional and multi-scale whiskers or / and granular ceramic reinforcements into the titanium alloy matrix and regulating their spatially ordered arrangement. They have excellent mechanical properties such as high specific strength, high stiffness, wear resistance, and high temperature resistance, and are used in high-end aerospace equipment.
[0003] Additive manufacturing technology, with its layered slicing and layer-by-layer deposition process based on three-dimensional models, realizes the integrated forming of parts with complex geometric structures, and has the advantages of high design freedom, high material utilization and high precision. Additive manufacturing technology for metal materials can be divided into three categories according to the different heat sources: laser, electron beam and arc additive manufacturing, which are widely used in the manufacture of large or complex components. The free forming and near-net forming characteristics of additive manufacturing technology provide a historic opportunity for the material-structure-performance integrated forming of lightweight, high-strength and difficult-to-deform titanium-based composite components.
[0004] At present, the raw materials for additive manufacturing of titanium-based composite materials are mainly powder materials, which are suitable for laser and electron beam additive manufacturing. Powder materials have the advantages of high forming precision, but they also have problems such as low deposition efficiency, low material utilization and high cost. In terms of powder pretreatment, commonly used methods include mechanical ball milling, electrochemical deposition and chemical vapor deposition. These methods embed or adsorb reinforcement reactants on the surface of titanium alloy powder by physical or chemical means, in order to form reinforcements through in-situ autogenous reactions during the additive manufacturing process. However, mechanical ball milling is easy to introduce impurities such as H and O, while electrochemical deposition and chemical vapor deposition are difficult to ensure the uniformity of reinforcements on the surface of titanium alloy powder. The above deficiencies in process preparation and powder pretreatment make the additive manufacturing of titanium-based composite materials based on powder materials have certain limitations. In comparison, fused wire additive has the advantages of high deposition efficiency (5kg / h) and dense organization, which is particularly suitable for high-efficiency and high-quality manufacturing of large-size structural parts. However, the matrix of high-strength titanium-based composite materials has a small number of slips (the α phase is an hcp structure), the interface of the reinforcement is easily mismatched, and the plasticity is low, making it almost difficult to draw into wires. At present, there is little research on the design and preparation technology of titanium-based composite wires. Therefore, how to prepare high-quality titanium-based composite wires and achieve stable fused wire additive manufacturing of lightweight, high-strength, and difficult-to-deform titanium-based composite components by regulating the matrix structure and the size distribution of the reinforcement has become the focus of researchers.
[0005] Some progress has been made in the research on fused additive manufacturing of metal-based composite materials and alloys. For example, patent CN115156551A discloses a method and system for arc additive manufacturing of particle-reinforced aluminum-based composite materials. The patent uses in-situ self-generated TiC particle-reinforced Al-6.3Cu alloy wire and ER2319 Al-6.3Cu alloy wire as additive manufacturing raw materials to prepare particle-reinforced aluminum-based composite materials. This method prepares a particle-reinforced aluminum-based composite ingot and directly draws it into a wire raw material for fused additive manufacturing. However, for titanium-based composite materials, the α phase in the titanium alloy matrix is a close-packed hexagonal structure with few slip systems and difficult deformation. It is easy to crack and brittle fracture during the drawing process, and it is difficult to directly use the "melt casting-drawing wire" method for additive manufacturing. Patent CN115781105A discloses a titanium alloy flux-cored welding wire and its flux core and preparation method. In this method, the powders of corresponding components, including 20-30 parts of aluminum powder, 50-60 parts of metal vanadium, 35-45 parts of metal chromium, 25-35 parts of metal zirconium, 0.8-1.2 parts of iron powder, and 25-35 parts of molybdenum powder, are mixed as filling powders, and the flux core is dried-the flux coating is rolled into a U-shaped groove-the flux powder is filled-the flux coating is closed-the diameter is reduced-the wire is drawn-the wire is taken up to obtain the titanium alloy flux-cored welding wire. However, this method can only obtain titanium alloy flux-cored welding wire, and titanium-based composite material wire cannot be obtained. At the same time, the uniformity of the mixed powder in this method will significantly affect the uniformity of the weld composition and structure based on this welding wire. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a continuous core mesh structure wire of a titanium-based composite material for fused wire additive manufacturing. The method helps to guide the direct preparation of high-strength and tough titanium-based composite materials and large-sized components thereof by fused wire additive manufacturing, and has important application value in major equipment fields such as aerospace.
[0007] The present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a titanium-based composite material continuous core mesh structure wire for fused wire additive manufacturing, comprising the following steps:
[0009] A. Use pure titanium strip or titanium alloy strip as the outer titanium shell;
[0010] B. Use titanium-based composite material powder embedded with fine mesh reinforcement as internal filling powder;
[0011] C. Rolling the titanium shell and the powder filled inside, and drawing and reducing the diameter to form a continuous core mesh structure wire;
[0012] D. Use fused filament additive manufacturing method to prepare in-situ reinforced titanium-based composites.
[0013] As an embodiment of the present invention, the thickness of the titanium strip in step A is 0.04-0.08 mm.
[0014] As an embodiment of the present invention, the material of the titanium strip includes pure titanium and titanium alloy. In some embodiments, the material of the titanium strip is at least one of Ti6Al4V, Ti-6.5Al-1.5Zr-3.5Mo-0.3Si, and Ti-5.8Al-4Sn-3.5Zr-0.7Nb-0.5Mo-0.35Si.
[0015] As an embodiment of the present invention, in step B, the titanium-based composite material powder has a powder particle size ranging from 53 to 150 μm.
[0016] As an embodiment of the present invention, the matrix of the titanium-based composite material powder comprises pure titanium and titanium alloy. The matrix is combined with a reinforcement to form a titanium-based composite material.
[0017] As an embodiment of the present invention, the reinforcement phase includes one or more reinforcements such as TiB, TiC and La2O3.
[0018] As an embodiment of the present invention, the titanium-based composite material is TiB / Ti6Al4V, TiC / Ti-6.5Al-1.5Zr-3.5Mo-0.3Si, (TiB+TiC) / Ti6Al4V or (TiB+La2O3) / IMI834.
[0019] As an embodiment of the present invention, the reinforcement phase is distributed in a network in the titanium-based composite material powder, and the size of the fine network structure is ≤10 μm.
[0020] As an embodiment of the present invention, the volume fraction of the reinforcement phase in the titanium-based composite material wire is 0.1 to 10 vol.%, preferably 0.1 to 5 vol.%.
[0021] As an embodiment of the present invention, the diameter of the continuous core mesh structure wire in step C is 1.2-3.0 mm. The diameter of the unit core mesh is ≤10 μm.
[0022] As an embodiment of the present invention, the drying temperature in the step of preparing the continuous core mesh structure wire material in step C is controlled at 200-400°C.
[0023] As an embodiment of the present invention, the drawing and reducing in step C comprises a method of roller die drawing, fixed die drawing, or a roller die and a fixed die combined in series.
[0024] As an embodiment of the present invention, the powder filling rate of the titanium-based composite material in the continuous core mesh structure wire preparation step in step C is 30-45%. If the powder filling amount is too low, pores will exist inside, affecting the subsequent use of the wire. If the powder filling amount is too high, it will cause surface cracks during the wire diameter reduction process.
[0025] As an embodiment of the present invention, in step C, the preparation of the continuous core mesh structure wire material comprises the following steps:
[0026] C1. Drying fine mesh titanium-based composite material powder;
[0027] C2, using roller extrusion to curl the titanium strip into a "U" shape;
[0028] C3, adding the titanium-based composite material powder of step C1 into a "U"-shaped titanium strip, and squeezing two sides of the "U"-shaped titanium strip together to form an "O"-shaped titanium tube;
[0029] C4. Directly place the titanium tube into the hot rolling die for initial diameter reduction to compact the powder core in the titanium tube;
[0030] C5, heating the rolling wheel to 400° C. to 450° C. by online heat treatment annealing, and performing multiple hot rolling to reduce the diameter of the titanium tube filled with the titanium-based composite material powder obtained in step C4 until the diameter reaches the designed size;
[0031] C6. Perform vacuum heat treatment on the titanium tube after the diameter reduction in step C5 to obtain titanium-based composite material wire.
[0032] In step C5, multi-pass hot rolling reduction refers to continuously heating rolling wheels of different reduction sizes (such as two rolling wheels of 3.6 mm, two rolling wheels of 3 mm, two rolling wheels of 2.5 mm, etc.) by induction heating, and maintaining the set temperature. The wire continuously passes through rolling wheels of different reduction sizes, which is a continuous rolling reduction process. The present invention designs the matrix component system and the type of additive body of the in-situ self-generated titanium-based composite wire by screening titanium-based composite powders with different reinforcements and volume fractions, and pure titanium or titanium alloy titanium strips of different thicknesses. In combination with this process, on the one hand, the diameter reduction is achieved, and on the other hand, the effect of stress relief annealing treatment is also achieved. Therefore, it is also called rolling wheel online heating annealing. In some embodiments, it is preferred to set the temperature to 400°C in the first online heating annealing, and the temperature increases during each treatment, and the online heating annealing temperature is 450°C at the last pass. This scheme can achieve a better stress relief annealing effect.
[0033] As an embodiment of the present invention, in step C5, auxiliary argon protection is performed during the hot rolling diameter reduction process.
[0034] As an embodiment of the present invention, in step C6, the temperature of the vacuum heat treatment is 500-650° C., and the time is 10-30 min.
[0035] As an embodiment of the present invention, the fuse additive manufacturing method described in step D includes one of arc fuse additive, laser fuse additive, and electron beam fuse additive.
[0036] The invention also provides an in-situ self-reinforced titanium-based composite material prepared by the method.
[0037] The method of the present invention designs the matrix component system and the type of additive of the in-situ self-generated titanium-based composite wire by screening titanium-based composite powders with different reinforcements and volume fractions, and pure titanium or titanium alloy titanium strips with different thicknesses. The titanium strip is used as an external shell, and the mesh structure reinforcement titanium-based composite powder is embedded. The titanium strip is firstly rolled into a "U" shape, and the titanium-based composite powder is added to the "U"-shaped titanium strip, and sealed and rolled into a titanium tube. The diameter is reduced by heat treatment annealing, hot rolling or drawing, and the operation steps are combined with heat treatment stress relief annealing cycle, and finally the wire of the required size is obtained by the diameter reduction process. Based on the continuous core mesh structure wire, the additive manufacturing is carried out, and the melting characteristics are regulated by changing the energy and distribution of different heat sources, thereby solving the problems of expensive powder raw materials, low density of prepared materials, and anisotropy of continuous fiber reinforced titanium-based composite materials based on wire additive manufacturing in the prior art.
[0038] In order to achieve the goal of preparing particle-reinforced titanium-based composite materials based on direct additive manufacturing of wires, the present invention adopts titanium-based composite material powder with embedded mesh reinforcement as filling powder, pure titanium or titanium alloy titanium strip as external titanium shell, and prepares titanium-based composite wire with a continuous core mesh structure of powder particle size based on U-tube rolling-filling powder-rolling sealing-rolling wheel online hot drawing and reducing diameter-annealing-winding and other process operations, so as to realize the preparation of titanium-based composite material components with controllable wire structure and adjustable reinforcement and alloy composition.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The present invention can design the matrix component system and the type of additive of the in-situ self-generated titanium-based composite wire by screening titanium-based composite powders with different reinforcements and volume fractions, as well as pure titanium or titanium alloy titanium strips with different thicknesses. It has the advantages of high design freedom and high material utilization rate, solves the problem of preparing titanium-based composite wires with difficult deformation and low plasticity of titanium alloys, and prepares titanium-based composite wires with a continuous core mesh structure.
[0041] (2) Compared with powder-based additive manufacturing processes, wire-based additive manufacturing has the advantages of high efficiency, high densification and low cost, and is also suitable for the integrated forming of large structural parts;
[0042] (3) The present invention is applicable to various types of unit-reinforced titanium-based composite materials, as well as titanium-based composite materials with mixed reinforcement containing different reinforcements, such as TiB, TiB+TiC and other TiB+La2O3 and other mixed reinforcement series;
[0043] (4) The present invention is applicable to pure titanium or titanium alloy substrates, including Ti, Ti-6Al-4V and Ti60, etc., and has a wide range of applications;
[0044] (5) The present invention is applicable to various additive manufacturing processes carried out under high-energy heat sources, such as arc additive manufacturing, laser additive manufacturing, and electron beam additive manufacturing, and realizes the integrated design and preparation of titanium-based composite materials based on wire materials;
[0045] (6) Based on the continuous core mesh structure titanium-based composite wire of the present invention, the melting, solidification and deposition processes are carried out layer by layer by additive manufacturing, and reinforcements of different types and sizes are generated in situ inside the titanium alloy by in-situ chemical reaction, thereby avoiding poor interface wettability and interface contaminants, improving the interface bonding strength between the reinforcement and the matrix, and obtaining an in-situ self-generated shape-controlling integrated high-strength and toughness titanium-based composite material;
[0046] (7) During the fused filament additive manufacturing process, the in-situ autogenous reaction of titanium-based composite wire-powder is used to refine the matrix grains and the size of the reinforcement, and the distribution of the reinforcement size is precisely controlled, thereby greatly improving the strength and toughness of the additively manufactured titanium-based composite material;
[0047] (8) The process of CN115781105A cannot overcome the problem of difficult deformation of titanium alloys; the reason is that when the filling powder is a titanium alloy powder with embedded reinforcement, its powder fluidity, surface hardness, deformation degree and other powder properties are significantly different from the mixed powder of CN115781105A, as well as traditional low-carbon steel and aluminum alloy and other metal materials with good plasticity and toughness; the high yield stress of the powder leads to severe shrinkage deformation during rolling and reducing diameter, which easily leads to stress concentration and local fracture of the pure titanium coating. The present invention reduces dislocation pile-up and stress concentration during high-temperature reducing diameter by online heat treatment and multiple annealing of the rolling wheel, and improves it by auxiliary multiple annealing during online hot drawing and reducing diameter of the rolling wheel, including online heating annealing of the rolling wheel and overall annealing after reducing diameter, so as to overcome the fracture problem caused by stress concentration during the deformation of titanium alloy and realize the optimized preparation of titanium-based composite wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0049] Figure 1 It is a schematic diagram of synthesizing a continuous core mesh structure titanium-based composite wire material based on the selected titanium strip and titanium-based composite powder with embedded mesh reinforcement according to the process of sealed rolling-drawing-online heat treatment-annealing;
[0050] Figure 2The prepared 2vol TiB+TiC / TC4 continuous core network structure titanium-based composite wire; (a) is the macroscopic morphology of the wire, (b) and (c) are the macroscopic morphology of the wire cross section and the local magnified image, (d) is the magnified image of the filling powder, (e) and (f) are the metallographic images of the wire cross section and the distribution map of the local network reinforcement, (g) is the schematic diagram of the three-dimensional morphology of the powder and the distribution map of the sample height difference;
[0051] Figure 3 Schematic diagram of the fused wire additive manufacturing process of in-situ self-reinforced titanium-based composite materials using continuous core mesh titanium-based composite wire; wherein, 1- welding gun, 2- continuous core mesh structure titanium-based composite wire, 3- wire feeding nozzle, 4- in-situ self-reinforced titanium-based composite material, 5- substrate;
[0052] Figure 4 The internal organization diagram of the titanium-based composite material prepared based on the continuous core mesh structure titanium-based composite material wire; wherein (a) is the internal organization in Example 2, and (b) is the internal organization in Comparative Example 2. DETAILED DESCRIPTION
[0053] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0054] Example 1
[0055] This embodiment provides a method for additive manufacturing of titanium-based composite materials based on continuous core mesh structure wire, and its preparation process is shown in Figure 1 ; including the following steps:
[0056] A. First, clean the titanium strip with a thickness of 0.04 mm with a mixture of NaOH and acetone, then rinse with clean water, and then use a mixed aqueous solution of HF and HNO3 for ultrasonic cleaning to obtain a cleaned TA1 titanium strip; the mass fraction of NaOH in the mixed solution of NaOH and acetone used is 15%, the mass fraction of acetone is 85%, the mass fraction of HF in the mixed aqueous solution of HF and HNO3 is 5%, and the mass fraction of HNO3 is 35%. Ultrasonic cleaning is performed for 2 minutes at a frequency of 20 kHz.
[0057] B. A 2.5 vol.% TiB+2.5 vol.% TiC reinforced TC4 composite material powder (5 vol TiB+TiC / TC4) prepared by an atomization method was selected, and a powder with a particle size of 53 to 80 μm was screened out through vibration screening; the embedded network reinforcement powder was dried at a temperature of 400°C for 2 hours.
[0058] C. Based on the preferred 0.04mm thick titanium strip and 5vol TiB+TiC / TC4 embedded mesh reinforcement powder, the titanium-based composite material powder dried in step B is filled into the U-shaped TA1 titanium strip by a flux-cored wire making machine, and the TA1 titanium strip is closed by a forming machine (i.e., the initial diameter reduction, compacting the powder core in the titanium tube), to obtain a 2vol TiB+TiC / TC4 titanium-based composite wire precursor with a continuous core mesh structure of 4mm in diameter (the powder accounts for 40% in the wire, and the other 60% is titanium strip, so the overall reinforcement content of the wire is 5vol.%×40%=2vol.%). The rolling wheel is heated to 400-450℃ by online heat treatment, and the TA1 titanium-based composite wire precursor with a diameter of 4mm is subjected to multiple hot drawing and diameter reduction, and argon protection is used during the diameter reduction process to avoid severe oxidation of the wire surface. Specifically, the rolling wheels with different diameter reduction sizes are continuously heated by induction heating, namely, two rolling wheels of 3.6 mm, maintained at 400°C, two rolling wheels of 3 mm, maintained at 415°C, two rolling wheels of 2.5 mm, maintained at 425°C, two rolling wheels of 2.2 mm, maintained at 435°C, and two rolling wheels of 2.0 mm, maintained at 450°C. The wire continuously passes through the rolling wheels with different diameter reduction sizes, and finally a welding wire with a diameter of 2.0 mm is obtained. The overall schematic diagram of the preparation process is shown as follows Figure 1 As shown, the cross-sectional macroscopic morphology and internal network reinforcement distribution of 2vol TiB+TiC / TC4 were prepared as shown in Figure 2 Finally, the reduced wire is transferred to a vacuum furnace for overall annealing after reducing the diameter. The stress relief annealing time is 30 minutes at a temperature of 500°C. The oil stains on the welding wire are wiped with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dried and coiled into a disc.
[0059] D. Based on the continuous core mesh structure titanium-based composite wire obtained above, the additive manufacturing is carried out by arc fuse additive manufacturing, based on REHM Tiger 180DC arc welding power source, welding current is 120A, welding speed is 3mm / s, wire feeding speed is 12mm / s, and reciprocating deposition strategy is adopted, that is, the deposition direction of the next deposition layer is opposite to that of the previous layer. The processing process is as follows Figure 3As shown, a continuous core mesh structure titanium-based composite wire 2 is fed to the arc of a welding torch 1 through a wire feeding nozzle 3, and melted and deposited to form an in-situ self-generated titanium-based composite material 5, and finally an in-situ self-generated reinforced titanium-based composite thin-walled part is prepared, and its internal structure is as shown in FIG. Figure 4 As shown in (a), the reinforcement is small and evenly distributed.
[0060] Example 2
[0061] This embodiment provides a method for additive manufacturing of a titanium-based composite material based on a continuous core mesh structure wire, comprising the following steps:
[0062] A. First, clean the titanium strip with a thickness of 0.04 mm with a mixture of NaOH and acetone, then clean it with clean water, and then use a mixed aqueous solution of HF and HNO3 for ultrasonic cleaning to obtain the cleaned TA1 titanium strip; the mass fraction of NaOH in the mixed solution of NaOH and acetone is 15%, the mass fraction of acetone is 85%, the mass fraction of HF in the mixed aqueous solution of HF and HNO3 is 5%, and the mass fraction of HNO3 is 35%. Ultrasonic cleaning is performed for 2 minutes at a frequency of 20kHz.
[0063] B. A 2.5 vol.% TiB-reinforced TC4 composite material powder prepared by an atomization method was selected, and a powder with a particle size of 80 to 100 μm was screened out through vibration screening; the embedded network reinforcement powder was dried at a temperature of 400° C. for 2 h.
[0064] C. Based on the preferred 0.04mm thick titanium strip and 2.5vol TiB / TC4 embedded mesh reinforcement powder, the titanium-based composite powder dried in step B is filled into the U-shaped TA1 titanium strip by a flux-cored wire making machine, and the TA1 titanium strip is closed by a forming machine (i.e., the initial diameter reduction, compacting the powder core in the titanium tube), to obtain a 1volTiB / TC4 titanium-based composite wire precursor with a continuous core mesh structure of 4mm in diameter. The rolling wheel is heated to 400-450℃ by online heat treatment, and the TA1 titanium-based composite wire precursor with a diameter of 4mm is subjected to multiple hot drawing and diameter reduction, and argon protection is used during the diameter reduction process to avoid severe oxidation of the wire surface. Specifically, the rolling wheels with different diameter reduction sizes are continuously heated by induction heating, namely, two rolling wheels of 3.6mm, maintained at 400℃, two rolling wheels of 3mm, maintained at 410℃, two rolling wheels of 2.5mm, maintained at 425℃, two rolling wheels of 2.2mm, maintained at 440℃, and two rolling wheels of 2.0mm, maintained at 450℃. The wire continuously passes through the rolling wheels with different diameter reduction sizes, and finally obtains the welding wire with a diameter of 2.0mm. Finally, the reduced wire is transferred as a whole to a vacuum furnace for overall annealing after the diameter reduction. The stress relief annealing time is 30min, the temperature is 500℃, and the oil stains on the welding wire are wiped with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dried and coiled into a disc.
[0065] D. Based on the continuous core mesh structure titanium-based composite material wire obtained above, laser fuse additive manufacturing was used for additive preparation. The process parameters of laser power of 1200 W and scanning speed of 300 mm / min were adopted. Based on the RC-LDM8060 laser additive manufacturing equipment, a reciprocating deposition strategy was adopted, that is, the deposition direction of the next deposition layer was opposite to that of the previous layer, so as to prepare in-situ self-reinforced titanium-based composite thin-walled parts.
[0066] Example 3
[0067] This embodiment provides a method for additive manufacturing of a titanium-based composite material based on a continuous core mesh structure wire, comprising the following steps:
[0068] A. First, clean the titanium strip with a thickness of 0.08 mm with a mixture of NaOH and acetone, then clean it with clean water, and then use a mixed aqueous solution of HF and HNO3 for ultrasonic cleaning to obtain the cleaned TA1 titanium strip; the mass fraction of NaOH in the mixed aqueous solution of NaOH and acetone is 15%, and the mass fraction of acetone is 85%. The mass fraction of HF in the mixed aqueous solution of HF and HNO3 is 5%, and the mass fraction of HNO3 is 35%. Ultrasonic cleaning is performed for 2 minutes at a frequency of 20kHz.
[0069] B. The 5 vol.% TiB reinforced TC4 composite material powder prepared by atomization method was selected, and the powder with a particle size of 100-120 μm was screened out by vibration screening; the embedded network reinforcement powder was dried at a temperature of 400° C. and a drying time of 2 h.
[0070] C. Based on the preferred 0.08mm thick titanium strip and 5vol TiB / TC4 embedded mesh reinforcement powder, the titanium-based composite powder dried in step B is filled into the U-shaped TA1 titanium strip by a flux-cored wire making machine, and the TA1 titanium strip is closed by a forming machine (i.e., the initial diameter reduction, compacting the powder core in the titanium tube), to obtain a 2volTiB / TC4 titanium-based composite wire precursor with a continuous core mesh structure of 4mm in diameter. The rolling wheel is heated to 400-450℃ by online heat treatment, and the TA1 titanium-based composite wire precursor with a diameter of 4mm is subjected to multiple hot drawing and diameter reduction, and argon protection is used during the diameter reduction process to avoid severe oxidation of the wire surface. Specifically, the rolling wheels with different diameter reduction sizes are continuously heated by induction heating, namely, two rolling wheels of 3.6mm, maintained at 400℃, two rolling wheels of 3mm, maintained at 410℃, two rolling wheels of 2.5mm, maintained at 420℃, two rolling wheels of 2.2mm, maintained at 430℃, two rolling wheels of 2.0mm, maintained at 440℃, and two rolling wheels of 1.6mm, maintained at 450℃. The wire material continuously passes through the rolling wheels with different diameter reduction sizes, and finally obtains the welding wire with a diameter of 1.6mm. Finally, the reduced wire material is transferred as a whole to a vacuum furnace for overall annealing after the diameter reduction. The stress relief annealing time is 30min, the temperature is 500℃, and the oil stains on the welding wire are wiped with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dried and coiled into a disc.
[0071] D. Based on the continuous core mesh structure titanium-based composite material wire obtained above, arc fuse additive manufacturing was used for additive preparation. Based on REHM Tiger 180DC arc welding power supply, welding current was 120A, welding speed was 3mm / s, wire feeding speed was 12mm / s, and reciprocating deposition strategy was adopted, that is, the deposition direction of the next deposition layer was opposite to that of the previous layer, to prepare in-situ self-reinforced titanium-based composite thin-walled parts.
[0072] Example 4
[0073] This embodiment provides a method for additive manufacturing of a titanium-based composite material based on a continuous core mesh structure wire, comprising the following steps:
[0074] A. First, clean the titanium strip with a thickness of 0.04 mm with a mixture of NaOH and acetone, then clean it with clean water, and then use a mixed aqueous solution of HF and HNO3 for ultrasonic cleaning to obtain a cleaned TA1 titanium strip; the mass fraction of NaOH in the mixed aqueous solution of NaOH and acetone is 15%, and the mass fraction of acetone is 85%. The mass fraction of HF in the mixed aqueous solution of HF and HNO3 is 5%, and the mass fraction of HNO3 is 35%. Ultrasonic cleaning is performed for 2 minutes at a frequency of 20 kHz.
[0075] B. The 2.5 vol.% TiB+2.5 vol.% La2O3 reinforced IMI834 composite material powder prepared by a gas atomization method was selected, and the powder with a particle size of 120-150 μm was screened out through vibration screening; the embedded network reinforcement powder was dried at a temperature of 400°C and a drying time of 2 h.
[0076] C. Based on the preferred 0.04mm thick titanium strip and 5vol TiB+La2O3 / IMI834 embedded mesh reinforcement powder, the titanium-based composite powder dried in step B is filled into the U-shaped TA1 titanium strip by a flux-cored wire making machine, and the TA1 titanium strip is closed by a forming machine (i.e., the initial diameter reduction, compacting the powder core in the titanium tube), to obtain a 2vol TiB+La2O3 / IMI834 titanium-based composite wire precursor with a diameter of 4mm continuous core mesh structure. The rolling wheel is heated to 400-450℃ by online heat treatment, and the TA1 titanium-based composite wire precursor with a diameter of 4mm is subjected to multiple hot drawing and diameter reduction, and argon protection is used during the diameter reduction process to avoid severe oxidation of the wire surface. Specifically, the rolling wheels with different diameter reduction sizes are continuously heated by induction heating, namely, two rolling wheels of 3.6mm, maintained at 400℃, two rolling wheels of 3mm, maintained at 410℃, two rolling wheels of 2.5mm, maintained at 420℃, two rolling wheels of 2.2mm, maintained at 430℃, two rolling wheels of 2.0mm, maintained at 440℃, and two rolling wheels of 1.6mm, maintained at 450℃. The wire material continuously passes through the rolling wheels with different diameter reduction sizes, and finally obtains the welding wire with a diameter of 1.6mm. Finally, the reduced wire material is transferred as a whole to a vacuum furnace for overall annealing after the diameter reduction. The stress relief annealing time is 30min, the temperature is 500℃, and the oil stains on the welding wire are wiped with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dried and coiled into a disc.
[0077] D. Based on the continuous core mesh structure titanium-based composite material wire obtained above, laser fuse additive manufacturing was used for additive preparation. The process parameters of laser power of 1500W and scanning speed of 500mm / min were adopted. Based on the RC-LDM8060 powder feeding laser additive manufacturing equipment, the continuous laser was changed to pulsed laser mode with a pulse frequency of 5Hz. The melting process was regulated by periodic solidification of the molten pool. At the same time, a 67° interlayer rotation deposition strategy was adopted, that is, the deposition direction of the next deposition layer differed by 67° from that of the previous layer, to prepare in-situ self-reinforced titanium-based composite thin-walled parts.
[0078] Example 5
[0079] This embodiment provides a method for additive manufacturing of a titanium-based composite material based on a continuous core mesh structure wire, comprising the following steps:
[0080] A. First, clean the titanium strip with a thickness of 0.08 mm with a mixture of NaOH and acetone, then clean it with clean water, and then use a mixed aqueous solution of HF and HNO3 for ultrasonic cleaning to obtain a cleaned TA1 titanium strip; the mass fraction of NaOH in the mixed solution of NaOH and acetone is 15%, and the mass fraction of acetone is 85%. The mass fraction of HF in the mixed aqueous solution of HF and HNO3 is 5%, and the mass fraction of HNO3 is 35%. Ultrasonic cleaning is performed for 2 minutes at a frequency of 20 kHz.
[0081] B. A 5 vol.% TiB reinforced TC4 composite material powder prepared by an atomization method was selected, and a powder with a particle size of 53 to 80 μm was screened out through vibration screening; the embedded network reinforcement powder was dried at a temperature of 400° C. for 2 h.
[0082] C. Based on the preferred 0.08mm thick titanium strip and 5vol TiB / TC4 embedded mesh reinforcement powder, the titanium-based composite powder dried in step B is filled into the U-shaped TA1 titanium strip by a flux-cored wire making machine, and the TA1 titanium strip is closed by a forming machine (i.e., the initial diameter reduction, compacting the powder core in the titanium tube), to obtain a 2volTiB / TC4 titanium-based composite wire precursor with a continuous core mesh structure of 4mm in diameter. The rolling wheel is heated to 400-450℃ by online heat treatment, and the TA1 titanium-based composite wire precursor with a diameter of 4mm is subjected to multiple hot drawing and diameter reduction, and argon protection is used during the diameter reduction process to avoid severe oxidation of the wire surface. Specifically, the rolling wheels with different diameter reduction sizes are continuously heated by induction heating, namely, two rolling wheels of 3.6mm, maintained at 400℃, two rolling wheels of 3mm, maintained at 410℃, two rolling wheels of 2.5mm, maintained at 420℃, two rolling wheels of 2.2mm, maintained at 430℃, two rolling wheels of 2.0mm, maintained at 440℃, and two rolling wheels of 1.6mm, maintained at 450℃. The wire material continuously passes through the rolling wheels with different diameter reduction sizes, and finally obtains the welding wire with a diameter of 1.6mm. Finally, the reduced wire material is transferred as a whole to a vacuum furnace for overall annealing after the diameter reduction. The stress relief annealing time is 30min, the temperature is 500℃, and the oil stains on the welding wire are wiped with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dried and coiled into a disc.
[0083] D. Based on the continuous core mesh structure titanium-based composite wire obtained above, electron beam fuse additive manufacturing was used for additive preparation. Based on the KL-106M electron beam fuse additive manufacturing equipment, the additive manufacturing process parameters were as follows: acceleration voltage 60 kV, beam current 50 mA, molten pool moving speed 1000 mm / min, wire feeding speed about 3 kg / h, overlap rate 30%, layer thickness 2 mm, vacuum pressure 5×10 -2 Pa. At the same time, a reciprocating deposition strategy is adopted, that is, the deposition direction of the next deposition layer is opposite to that of the previous layer, to prepare in-situ self-reinforced titanium-based composite thin-walled parts.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is that: the titanium-based composite material powder of Example 1 is used, and multiple online annealing is not used in the drawing process, and only conventional drawing in the art is used. Based on 2.5vol.% TiB+2.5vol.% TiC reinforced TC4 composite material powder (5vol TiB+TiC / TC4), a TA1 titanium strip is closed by a forming machine to obtain a 2vol TiB+TiC / TC4 titanium-based composite material wire precursor with a continuous core mesh structure of 4mm in diameter. The TA1 titanium-based composite wire precursor with a diameter of 4mm is continuously cold-drawn and reduced in diameter on a wire drawing machine, and passes through reducing wheels with diameters of 3.8mm, 3.4mm, and 3.0mm in turn. After each cold-drawing and reducing, it is stress-relieved in a vacuum tube annealing furnace for 40min, and the annealing temperature is 600℃. However, this comparative example should only be able to obtain a diameter of 3.0mm, and cracks will appear if the diameter is further reduced. Wipe the oil stains on the welding wire with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dry and coil it into a disc. Based on the titanium-based composite wire obtained above, the additive preparation was carried out by arc-fused wire additive manufacturing. Based on the REHM Tiger 180DC arc welding power source, the welding current was 120A, the welding speed was 3mm / s, the wire feeding speed was 12mm / s, and the reciprocating deposition strategy was adopted, that is, the deposition direction of the next deposition layer was opposite to that of the previous layer, to prepare in-situ self-reinforced titanium-based composite thin-walled parts. When this method is used for additive manufacturing, the raw material powder is easily oxidized during the ball milling process, and the powder uniformity is difficult to ensure, which leads to uneven distribution of reinforcements in the prepared in-situ self-reinforced titanium-based composite material. At the same time, due to the lack of multiple annealing treatments (including rolling online hot drawing annealing and overall annealing), it is difficult to further reduce the wire diameter. The morphology of the deposited layer in additive manufacturing based on large-diameter wire is difficult to accurately control, resulting in poor stability and anisotropy of mechanical properties, which affects the further development and application of additive manufacturing integrated titanium-based composite structural parts.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is that titanium-based composite material powder with a particle size range of 15 to 45 μm is used as a filling material to fill the U-shaped titanium strip. The remaining steps are basically the same as Example 1. The TA1 titanium strip is closed by a forming machine to obtain a 2vol TiB+TiC / TC4 titanium-based composite material wire precursor with a diameter of 4 mm. The rolling wheel is heated to 400-450°C by online heat treatment, and the TA1 titanium-based composite wire precursor with a diameter of 4 mm is subjected to multiple hot drawing and diameter reduction. At the same time, argon gas protection is used during the diameter reduction process to avoid severe oxidation of the wire surface. The specific operation is the same as Example 1, and a welding wire with a diameter of 2.0 mm is obtained; finally, the wire after diameter reduction is transferred as a whole to a vacuum furnace for overall annealing after diameter reduction. The stress relief annealing time is 30 minutes and the temperature is 500°C; the oil stains on the welding wire are wiped with a cotton cloth dipped in acetone or anhydrous ethanol, and finally dried and coiled into a disc. Based on the titanium-based composite wire obtained above, the additive preparation was carried out by arc-fused wire additive manufacturing, based on REHM Tiger 180DC arc welding power source, welding current of 120A, welding speed of 3mm / s, wire feeding speed of 12mm / s, and reciprocating deposition strategy, that is, the deposition direction of the next deposition layer is opposite to that of the previous layer, to prepare in-situ self-reinforced titanium-based composite thin-walled parts. When this method is used for additive manufacturing, due to the small particle size of the raw material powder, the molecular attraction and electrostatic attraction between the powders are large, which makes it easy for the particles to adsorb and aggregate into agglomerates, and the adhesion is increased, which makes the fluidity of the filling powder worse, and it is difficult to be evenly distributed in the continuous core mesh structure titanium-based composite wire, which leads to uneven distribution of reinforcements in the preparation of in-situ self-reinforced titanium-based composite materials, such as Figure 4 As shown in (b), defects such as pores and microcracks may occur, which seriously deteriorate the mechanical properties of the additive body.
[0088] In summary, the additive manufacturing method provided by the present invention can refine the matrix grains and the size of the reinforcement through the in-situ autogenous reaction during the melting process of the titanium-based composite wire with a continuous core mesh structure, and can achieve precise control of the size distribution of the reinforcement, thereby greatly improving the strength and toughness of the additively manufactured titanium-based composite material. Specifically, (1) Embedded mesh reinforcement design: The present invention adopts titanium-based composite powder with embedded fine mesh reinforcement, which effectively solves the problem of poor wettability between the reinforcement and the matrix and powder agglomeration, and realizes the uniform distribution and precise control of the reinforcement in the matrix. (2) Continuous core mesh structure: Through the rolling and drawing of titanium strips and titanium-based composite powders, a continuous core mesh structure is formed, which improves the strength and toughness of the wire and facilitates the subsequent additive manufacturing process. (3) Process parameter optimization: The present invention optimizes the drying temperature, filling rate, diameter reduction process, heat treatment process, etc. to ensure the quality and performance of the wire. It can be seen that the method of the present invention has the advantages of high design freedom and high material utilization, and provides opportunities for the integrated preparation of complex components of high-strength and tough titanium-based composite materials.
[0089] It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments may be combined with each other at will.
Claims
1. A method for preparing a continuous core mesh structure wire for fused filament additive manufacturing, characterized in that: The following steps are involved: A. Use titanium strip as the outer titanium shell; B. Use fine mesh titanium-based composite material powder as internal filling powder; C. Rolling the titanium shell and the powder filled inside, and drawing and reducing the diameter to form a continuous core mesh structure wire; D. Use fused filament additive manufacturing method to prepare in-situ reinforced titanium-based composites.
2. The method according to claim 1, characterized in that The thickness of the titanium strip in step A is 0.04-0.08 mm; the material of the titanium strip includes pure titanium and titanium alloy; the titanium alloy includes Ti6Al4V, Ti-6.5Al-1.5Zr-3.5Mo-0.3Si, and Ti-5.8Al-4Sn-3.5Zr-0.7Nb-0.5Mo-0.35Si.
3. The method according to claim 1, characterized in that In step B, the titanium-based composite material powder has a powder particle size ranging from 53 to 150 μm.
4. The method according to claim 1, characterized in that: In step B, the titanium-based composite material powder, whose matrix includes pure titanium and titanium alloy, is combined with a reinforcement to form a titanium-based composite material.
5. The method according to claim 4, characterized in that The titanium-based composite material powder includes at least one of the following technical features: B1, the reinforcement includes one or more of TiB, TiC and La2O3; B2, titanium-based composite materials are TiB / Ti6Al4V, TiC / Ti-6.5Al-1.5Zr-3.5Mo-0.3Si, (TiB+TiC) / Ti6Al4V or (TiB+La2O3) / IMI834; B3. The reinforcement is distributed in a network in the titanium-based composite powder, and the size of the fine network structure is ≤10μm; B4. The volume fraction of the reinforcing phase in the titanium-based composite material powder is 0.1 to 10 vol.%.
6. The method according to claim 1, characterized in that In step C, The diameter of the continuous core mesh structure wire is 1.2-3.0 mm, and the unit core mesh diameter is ≤10 μm; And / or, the drawing and reducing method includes roller die drawing, fixed die drawing, or a combination of a roller die and a fixed die in series.
7. The method according to claim 1, characterized in that In step C, the preparation of the continuous core mesh structure wire material includes the following steps: C1. Drying fine mesh titanium-based composite material powder; C2, using roller extrusion to curl the titanium strip into a "U" shape; C3, adding the titanium-based composite material powder of step C1 into a "U"-shaped titanium strip, and squeezing two sides of the "U"-shaped titanium strip together to form an "O"-shaped titanium tube; C4. Directly place the titanium tube into the hot rolling die for initial diameter reduction to compact the powder core in the titanium tube; C5, heating the rolling wheel to 400° C. to 450° C. by online heat treatment annealing, and performing multiple hot rolling to reduce the diameter of the titanium tube filled with the titanium-based composite material powder obtained in step C4 until the diameter reaches the designed size; C6. Perform vacuum heat treatment on the titanium tube after the diameter reduction in step C5 to obtain titanium-based composite material wire.
8. The method according to claim 7, characterized in that In step C5, auxiliary argon protection is provided during the hot rolling and diameter reduction process; And / or, the temperature of vacuum heat treatment is 500-650° C., and the time is 10-30 min.
9. The method according to claim 1, characterized in that: The fuse additive manufacturing method described in step D includes one of arc fuse additive, laser fuse additive, and electron beam fuse additive.
10. An in-situ reinforced titanium-based composite material prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Titanium alloy flux-cored wire and flux core and preparation method thereof
CN115781105A
Welding method for argon tungsten-arc welding of net structural bi-based composite material
CN104942407A
Additive manufacturing method based on titanium and titanium alloy wires
CN105108339A
Additive manufacturing method for titanium-based composite with self-generating ultrafine mesh structure reinforcement
CN111151746A
Method for additive production of articles from titanium alloys with a functional gradient structure
RU2700439C1
Cited By
Spherical silver-copper-titanium metal powder and preparation method thereof
CN120587468A
High-strength titanium alloy powder core wire material special for additive manufacturing and preparation method of component of high-strength titanium alloy powder core wire material
CN121669957A
A high-strength titanium alloy powder core wire special for additive manufacturing and a preparation method of a component thereof
CN121669957B